Morphological and Molecular Identification of Root-knot Nematode, Meloidogyne incognita Infecting Pomegranate (Punica granatum L.) in Jodhpur, Rajasthan, India - Basant Deshwal; Gautam Chawla; Kavalipurapu Kranti K. V. V. S. (Archives of Current Research International, 2024)
Root-knot nematodes (Meloidogyne spp.) pose a major threat to pomegranate (Punica granatum L.) cultivation in India, leading to significant yield losses. In this study, galled roots of pomegranate were collected from orchards in Jodhpur, Rajasthan and nematode infestation was confirmed through root staining. The perineal pattern of females displayed the typical characteristics of the Meloidogyne incognita. To further confirm the species, DNA was extracted and a polymerase chain reaction (PCR) assay using species-specific SCAR (sequence-characterized amplified region) primers was conducted. The M. incognita- species specific primers, MincF1/MincR1, yielded the expected 150 bp product, verifying the presence of M. incognita. This study marks the first molecular confirmation of M. incognita infecting pomegranate orchards in this region, demonstrating the efficacy of SCAR markers in complementing traditional morphological identification as well.